2005
DOI: 10.1007/s11115-005-0953-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comparisons on the Satisfaction of Interscholastic Coaches of Girls’ Sports

Abstract: According to previous work in the coaching field, job satisfaction has been found to be an important work related variable, critical to retention and turnover of female coaches [Chelladurai, P., and E. Ogasawara. (2003). “Satisfaction and Commitment of American and Japanese Collegiate Coaches.” Journal of Sport Management 17, 62–73; Sagas, M., and F.B. Ashley. (2001). “Gender Differences in the Intent to Leave Coaching: Testing the Role of Personal, External, and Work-Related Variables.” International Journal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…At the high school level, Smucker and Whisenant (2005) found men held a majority of the coaching positions over girls' sports and virtually all positions over boys' sports. In Texas in 2005, males even held the dominant number of coaching positions of female sports according to Smucker and Whisenant.…”
Section: Current Status Of Women In Sports Leadershipmentioning
confidence: 98%
See 1 more Smart Citation
“…At the high school level, Smucker and Whisenant (2005) found men held a majority of the coaching positions over girls' sports and virtually all positions over boys' sports. In Texas in 2005, males even held the dominant number of coaching positions of female sports according to Smucker and Whisenant.…”
Section: Current Status Of Women In Sports Leadershipmentioning
confidence: 98%
“…In order to ensure that all promising female athletic administrators have access to mentors, the professional organizations can provide a concrete structure to support this professional growth. Smucker and Whisenant (2005) found that without opportunities to develop a mentorship, women reduced their opportunities to lead. In fact, six of the eight participants had a strong, influential male mentor early in their career.…”
Section: Organize and Involve Women In Mentoring Programsmentioning
confidence: 99%
“…The process of referent selection was also seen with interscholastic coaches of girls' sports. Smucker and Whisenant (2005) , 1999). Further, the existing and very limited sports-related job satisfaction research has been general in nature as opposed to reviewing particular job positions such as athletic marketing director roles.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…All coaches held the required license to train at these age groups. We selected exclusively male Without university studies related with PESS 0 0 0 coaches to control the potential differences in communication and coaching styles between male and female coaches reported in several studies (Millard, 1996;Smucker and Whisenant, 2005;Bolter and Lucas, 2018). We used this sample size without an a priori power analysis.…”
Section: Participantsmentioning
confidence: 99%